The Ability of Students' in Using Length Measuring Instruments at State High School - oktaviani, defianti; Ngadimin, Ngadimin; Halim, A (Universitas Syiah Kuala, 2020)
The purpose of this study was to determine the ability of students to use length measuring instruments at the State High School 7 Banda Aceh. This type of research was descriptive with a qualitative approach. The population in this study were all students of class X in State High School 7 Banda Aceh. The sampling technique in this study uses random sampling. The samples taken in this study were students from class X which totaled 5 classes, each class was taken 5 students who were randomly selected as samples. Data collection techniques by providing multiple choice tests of 10 questions and skills tests. Data collection techniques used were knowledge tests in the form of objective tests in the form of multiple choice and skills tests. The technique in data processing uses percentages to get the results of this study. Based on the results of the study it can be concluded that the ability of students' knowledge to use length measuring instruments by 60% and to use the calipers by 55%. While knowledge on screw micrometers by 72% and skills using screw micrometers by 63%. So it can be concluded that the grade X students of State High School 7 Banda Aceh had pretty good knowledge and skills in using calipers, while the knowledge and skills of students on the micrometer screw was good.Keywords:basic length measuring, physics education, instruments